Pelestarian Bahasa Lokal Pada Usaba Sambah di Desa Adat Tenganan Dauh Tukad, Karangasem - Ni Wayan Kertiasih; A.A. Inten Mayuni; I Made Mardika (Universitas Warmadewa, 2022)
Community service in Tenganan Dauh Tukad Village aims to empower the community in preserving the local language, especially local terms in the usaba sambah ceremony. The benefits of service are to grow public awareness, especially the younger generation, to preserve the cultural traditions they have, such as the tradition of megeret pandans or pandan wars. The preservation of cultural traditions economically also has an impact on the development of tourism in the village of Tenganan Dauh Tukad. The arrival of these tourists has an impact on the income of the traditional village, including the local community in the Tenganan Dauh Tukad Traditional Village. The solutions offered to overcome the problem are (1) Giving lectures to the Truna sekaa and Daha sekaa about the preservation of the local language. (2) Providing assistance in the preservation of local languages, (3) Documenting local languages and their cultural backgrounds so that they can be understood by the local community. The outputs produced are articles in national journals with ISSN, activity videos, publications in print media, increased application of science and technology.